The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s1751731117001100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding long or short wheat hay v. wheat silage in the ration of lactating cows on intake, milk production and digestibility

Abstract: The objective of this study was to evaluate in lactating cows the effect of either chopping or ensiling of wheat roughage on: intake, digestibility, lactation performance and animal behavior. Three groups of 14 lactating cows each, were fed total mixed rations (TMRs) based on either long wheat hay (HL), short wheat hay (HS) or wheat silage (SI), as the sole roughage source (30% of TMR dry matter (DM)). Parameters examined: sorting behavior, DM intake, milk yield and composition, rumination, recumbence, average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The cows were grouped for similar physical conditions-age in months, body weight, and daily milk production-and were at the same stage of lactation. The cows were fed diets consisting of 30% forage and 70% concentrate that differed in their forage source and chop length, as described by Shaani et al [22], and fed a total mixed ration ad libitum, provided once a day. Two cows belonging to two different groups were excluded from the experiment due to veterinary considerations.…”
Section: Animal Handling and Samplingmentioning
confidence: 99%
“…The cows were grouped for similar physical conditions-age in months, body weight, and daily milk production-and were at the same stage of lactation. The cows were fed diets consisting of 30% forage and 70% concentrate that differed in their forage source and chop length, as described by Shaani et al [22], and fed a total mixed ration ad libitum, provided once a day. Two cows belonging to two different groups were excluded from the experiment due to veterinary considerations.…”
Section: Animal Handling and Samplingmentioning
confidence: 99%
“…To control costs alternative forms of animal feed need to be urgently identified. Wheat ( Triticum aestivum L.) is a versatile crop that is used for grain, pasture, or silage in worldwide ( Shaani et al, 2017 ). It presents a high nutritive value, protein content, productivity, and digestibility and also contains good vitamins concentrations and fiber digestibility or even significantly higher than hay and corn ( Crovetto et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that the digestibility of neutral detergent fiber (NDF) tended to be lower in hay than silage, yet feeding hay increased the total feed intake, milk yield and nitrogen efficiency in dairy cows, as compared to silage [ 8 ]. Shaani et al [ 9 ] also concluded that short WCWH could be a better forage source than whole crop wheat silage due to greater feed intake. These studies demonstrated that WCWH should be a better feed source than whole crop wheat silage for ruminants.…”
Section: Introductionmentioning
confidence: 99%